Designing the technology of pastous milk-containing foodstuffs for the diets of military personnel - Polishchuk, Galyna; Simahina, Galina; Naumenko, Nataliia; Ustymenko, Ihor (My University, 2016)
The composition and method of obtaining food emulsions used for the normalization of mixtures in the production of various types of milk-containing products, including for military personnel, have been developed.
Keywords: харчова емульсія; пищевая эмульсия; food emulsion; раціон військовослужбовців; рацион военнослужащих; ration of military personnel; молоковмісний продукт; молокосодержащий продукт; milk-based product; кафедра технології молока і молочних продуктів; кафедра технології оздоровчих продуктів